Mitigating Rural Poverty in Taraba State: Informal Economy to the Rescue - Oromareghake, Patrick B.; Enganya, Yakubu; Yerima, Mary; Maikomo, John Moses; Dabale, Jesse Dearsley (Darul Yasin Al Sys, 2025)
This study examines the relationship between informal enterprises and rural poverty in Taraba State, Nigeria, within the context of widespread deprivation marked by hunger, malnutrition, inequality, and infrastructural deficits, particularly in rural communities. Guided by the rational choice paradigm, the research explores how informal sector activities can serve as a viable strategy for poverty alleviation. Data were collected from business premises in five areas of Jalingo metropolis: ATC, Mile 6, Mayo Dassa, Mayo Gwoi, and Magami, selected for their distinctive characteristics and concentration of informal economic activities. Statistical tables were used for data presentation, while a descriptive approach was employed for analysis. Findings reveal that informal enterprises, when encouraged and properly coordinated, can significantly contribute to reducing rural poverty. The study recommends that policymakers provide financial support, essential infrastructure, and an enabling environment for informal sector growth, as it holds substantial potential for minimizing poverty levels in rural communities.